Uji Efektifitas Pestisida Nabati Biji Mimba (Azadirachta indica A. Juss) terhadap Hama yang Menyerang Selada Merah (Lactuca sativa var. acephala) - Raja Malem Kata Keliat; A.A. Ayu Agung Sri Sunari; Ni Nengah Darmiati (Nandur, 2024)
The purpose of this study is to determine the type (species) of pests that attack red lettuce plants (Lactuca sativa var. acephala), knowing the effect of neem seed vegetable pesticide application in controlling pests on red lettuce and knowing the concentration of neem seed vegetable pesticides that are most effective in controlling pests on red lettuce plants. The research was conducted from May to June 2023 on the land of Biaung Village, Pemanis Hamlet, Penebel District, Tabanan Regency which is located at 8°-24'33-5"- 8°- 40'91-36" south latitude and 115°-10'13-0"- 115°-17'02-84" east longitude. The study used the Group Randomized Design method, namely neem seed vegetable pesticides with 6 repeats and the concentration used was a stratified concentration including 0% (control), 5%. 10%, and 15%. Based on the results of observations, the types of pests that attack red lettuce plants, are Valanga nigricornis, Atractomorpha crenulate, Ariolimax columbianus. The results showed that the application of vegetable pesticides neem seed extract was not able to control pest attacks on red lettuce plants.